The Nazi-Fascist New Order for European Culture - Martin, Benjamin G. (2016)
Following France’s defeat, the Nazis moved forward with plans to reorganize a European continent now largely under Hitler’s heel. Some Nazi elites argued for a pan-European cultural empire to crown Hitler’s conquests. Benjamin Martin charts the rise and fall of Nazi-fascist soft power and brings into focus a neglected aspect of Axis geopolitics.